Pengaruh Perilaku Konsumen Terhadap Keputusan Pembelian Produk, Harga, Dan Promosi - Benius Benius; Pupu Iswandiyah Raysharie; Adis Brilianti; Devita Sari Sirait; Febrina Putri Lestari; Justin Samuel Laurent; Mella Anugrahni; Muhammad Riko Imansyah; Putri Lestari (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Technology is changing the times, and in the future this change is accompanied by an increase in diverse needs and desires, especially shopping needs. Related to this, it also affects the behavior patterns of consumers who make decisions in buying a product. The company has the opportunity to make a profit to maintain its business continuity if the level of sales to consumers is high, whereas if the level of sales to consumers is low, the company will lose money and will ultimately fail to survive. Market competition expects companies to find ways to make their products sell well in the market and have a place in the hearts of buyers. The results of the literature review show that product, price, and promotion affect consumer behavior. This is expected to provide insight to marketers to understand and meet consumer preferences and develop more effective strategies to optimize the most influential marketing variables. Keywords: Consumer Behavior, Product, Price, And Promotion